Mind wandering at encoding, but not at retrieval, disrupts one-shot stimulus-control learning - Whitehead, Peter S. (Atten Percept Psychophys, 2021)
The one-shot pairing of a stimulus with a specific cognitive control process, such as task switching, can bind the two together in memory. The episodic control-binding hypothesis posits that the formation of temporary stimulus-control bindings, which are held in event-files supported by episodic memory, can guide the contextually appropriate application of cognitive control. Across two experiments, we sought to examine the role of task-focused attention in the encoding and implementation of stimulus-control bindings in episodic event-files. In Experiment 1, we obtained self-reports of mind wandering during encoding and implementation of stimulus-control bindings. Results indicated that, whereas mind wandering during the implementation of stimulus-control bindings does not decrease their efficacy, mind wandering during the encoding of these control-state associations interferes with their successful deployment at a later point. In Experiment 2, we complemented these results by using trial-by-trial pupillometry to measure attention, again demonstrating that attention levels at encoding predict the subsequent implementation of stimulus-control bindings better than attention levels at implementation. These results suggest that, although encoding stimulus-control bindings in episodic memory requires active attention and engagement, once encoded, these bindings are automatically deployed to guide behavior when the stimulus recurs. These findings expand our understanding of how cognitive control processes are integrated into episodic event files. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.3758/s13414-021-02343-9.